Nourishing Critical Thinking Skills using Neuro-Linguistic Programming - Farah Hashmi (PJE, 2023)
Neuro-Linguistic Programming (NLP) is a widely used approach, introduced by Bandler and Grinder (1970). In this study, the researcher explores different techniques involved in NLP, which can be utilized by teachers in teaching different genres of literature such as drama, prose, etc. In this quasi-experimental research, the researcher selected two groups: one experimental group consisting of 108 students, and the other a control group consisting of 141 students, enrolled in the Master’s Program in English Literature and Linguistics. The sample was selected through random sampling.